Adsorption of Uranium(VI) from Aqueous Solution by Modified Rice Stem - Zhang Xiao-teng; Jiang Dong-mei; Xiao Yi-qun; Chen Jun-chang; Hao Shuai; Xia Liang-shu (Journal of Chemistry)
The biosorption is an effective and economical method to deal with the wastewater with low concentrations of uranium. In this study, we present a systematic investigation of the adsorption properties, such as the kinetics, thermodynamics, and mechanisms, of modified rice stems. The rice stems treated with 0.5 mol/L NaOH solutions show higher removal percentage of uranium than those unmodified under the conditions of initial pH (pH = 4.0), absorbent dosage (5–8 g/L), temperature (T = 298 K), and adsorption equilibrium time (t = 180 min). The removal percentage of uranium(VI) decreases with increasing initial concentration of uranium(VI). The Langmuir isotherm model, which suggests predominant monolayered sorption, is better than Freundlich and Temkin models to elucidate the adsorption isotherm of adsorbed uranium. Kinetic analyses indicate that the uranium(VI) adsorption of the modified rice stem is mainly controlled by surface adsorption. The pseudo-second-order kinetic model, with the correlation coefficient of R2 = 0.9992, fits the adsorption process much better than other kinetic models (e.g., pseudo-second-order kinetic model, Elovich kinetic model, and intraparticle diffusion model). The thermodynamic parameters ΔG0, ΔH0, and ΔS0 demonstrate that the adsorption of uranium(VI) is an endothermic and spontaneous process, which can be promoted by temperature. The adsorption of uranium can change the morphology and the structure characteristics of the modified rice stem through interaction with the adsorption sites, such as O-H, C=O, Si=O, and P-O on the surface.